Auditoria de control interno y su incidencia en el área administrativa de la coooperativa ahorro y crédito futuro Lamanense, cantón La Maná año 2013. - Briones Perez, Amalia Marcelina (2015)
This research project was carried out in Canton La Mana, Cotopaxi province. As usual commonly used to perform an audit of internal control for the administrative area of the Cooperative Savings and Credit Lamanense Future Year 2013. The research was conducted over a period of 240 days and corresponds to an inductive-deductive, corresponding to the internal control analysis was wont general objective evaluear Internal Control and its effect on the decision making process within the credit union "Future Lamanense Canton La Mana to meet the objectives set in the present investigation, the methods used for bibliographic research and field specifically because I stayed at the scene Relevant data were collected profundisando research on internal control by the situational analysis to identify possible policies and procedures to guide the collaborators of the Administrative area to make your work eficas to obtain a consistent and systematic process activities. Data and information recompilaron about project Development, Research deepen the internal control, meaning that the diagnosis of Cooperative Savings and Credit Lamanense Future 2013, has allowed the identification of their duties, Policies and Procedures, para Obtain process activities systematic and consistent UN Work Collaboration Guien a sea of administrative area and effective and efficient way have the benefit of the cooperative